Pengaruh Literasi Keuangan, Inklusi Keuangan, Digital Payment, Kapabilitas Teknologi Informasi Komunikasi, dan Kapabilitas Keuangan Digital Terhadap Kinerja UMKM Kuliner di Kecamatan Banyumanik Kota Semarang - Shinfi Nabila Putri; Enny Susilowati Mardjono; Ira Septriana; Purwantoro Purwantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effects of financial literacy, financial inclusion, digital payment, information and communication technology (ICT) capability, and digital financial capability on the performance of micro, small, and medium enterprises (MSMEs) in Banyumanik District. This research employs a quantitative approach using primary data collected through purposive sampling, with a sample of 100 MSME owners registered on digital platforms. The data were analyzed using SPSS statistical analysis techniques. The findings indicate that, partially, digital payment and information and communication technology (ICT) capability have a positive and significant effect on MSME performance, while financial literacy, financial inclusion, and digital financial capability do not have a significant effect. Simultaneously, all variables have a significant effect on MSME performance, indicating that the combination of financial factors and digital capabilities continues to play an important role in enhancing MSME performance and sustainability.